Middle East and African Student (MEAS) perceptions of Islam and Islamic moderation: a case study - Mansoureh Ebrahimi; Kamaruzaman Yusoff; Rozmi Ismail (IAIN Salatiga, 2021)
Islamic Moderation is such a fundamental concept that without it understanding faith is inadequate at best. Muslims are required by definition of the term ‘Muslim’ to remain on the middle path in everything pertaining to the life ways. They must not overstep the bounds (tafrit) and become trapped in the extremist quagmire (ifrat). As an Islamic doctrine par excellence, moderation inherently finds solutions for injustice and the violation of human rights. Nonetheless, some schools of Islamic thought (madhhabs) attend extremist ideology, particularly those of Middle East and African savour. These have spread a frightful spirit of intolerance throughout the world that has indelibly blackened Islam’s image by choosing to deny Islam’s characteristic spirit of moderation. In so doing, they marginalize any proper implementation of authentic Islam and block all corrective political discourse. Militant radicals clearly neglect moderation as a doctrinal position that is traditionally essential to the creed. This paper presents a broad exposure to Islam’s middle path with a focus on 192 respondents in a survey taken by Middle Eastern and African students (MEAS) studying in Malaysia. Qualitative and quantitative approaches were used to achieve four significant findings indicating these students do not understand the nature of being a good Muslim.